The Chinoiserie style and its interpretations in urban park design from a historical and contemporary perspective, based on selected examples - Krupa Michał; Ivashko Yulia (Technical Transactions)
This paper discusses landscape design inspired by Chinese tradition and symbolism. The authors briefly presented the basics of Chinese tradition in the establishment of gardens and parks, their elements, symbolism and the messages they convey, in the context of the interpretation of these traditions in the design of parks established in the Chinoiserie style outside China, mainly in Europe, both in the past and at present. This study also explores the problem of the poor state of the environment, especially in urban areas, which is largely related to the shortage of green space, including parks and gardens. The lack of these spaces and, at the same time, the need to create recreational yet visually appealing spaces for the urban bourgeoisie has led to a re-emergence of Chinese landscape design traditions. One example of a contemporary implementation of a Chinoiserie-style garden is the Monte Palace Tropical Garden in Funchal, the capital of Madeira.